2009
DOI: 10.1007/s00464-009-0711-0
|View full text |Cite
|
Sign up to set email alerts
|

The esophageal hiatus: what is the normal size?

Abstract: The mean HSA was determined in these normal subjects to be 5.84 cm(2). It was directly proportional to chest circumference and independent of height, weight, BMI, and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
2
14
0
3
Order By: Relevance
“…Batirel et al estimated that the expected HSA after crural repair should be 2.5–3.0 cm 2 , which is in agreement with our normal size [7]. Shamiyeh et al found mean HSA of 5.84 cm 2 among cadavers [15]. …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Batirel et al estimated that the expected HSA after crural repair should be 2.5–3.0 cm 2 , which is in agreement with our normal size [7]. Shamiyeh et al found mean HSA of 5.84 cm 2 among cadavers [15]. …”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have approximated HSA using the geometric assumption that the hiatus is shaped like a slice of a circle whose area can be calculated after obtaining the radius and angle, a method first described by Granderath et al in 2007. [811, 1315]. Others have estimated HSA by tracing the region of interest on an intra-operative image with a graphic software [7].…”
Section: Introductionmentioning
confidence: 99%
“…In our experience, the value of HSA in normal and in obese subjects (mean values: 4.19 and 3.92 cm 2 , respectively) was higher than those reported by Quyang (mean 2.5 cm 2 ), but similar to the dimensions found by other authors [2,3,14] while mean HSA was definitely larger in patients with demonstrated HH (mean 8.3 cm 2 ). As reported by Shamiyeh, a mean HSA of 5.84 cm 2 was found in the cadavers of overweight (BMI 27 kg/m 2 ) subjects [14] with no HH, but the difference might be explained by the physiological status of the tissues. Batirel proposed a postoperative value target of 2.5-3.0 cm 2 after the surgical reparation of the hiatal defect [2].…”
Section: Discussionsupporting
confidence: 87%
“…Granderath first introduced the concept of measuring the HSA in 2007 by using an adapted intraoperative formula [3]. It was then modified by others, who introduced further intraoperative measuring methods, all with the goal to offer a tailored approach, based on the HSA values, for the antireflux surgery, which could be simple cruroplasty, reinforced with mesh or tension-free with mesh [2,14,15]. Our intraoperative formula, although simplified, provides relatively the same measurement as Granderath's formula, with a small error that does not alter the results, as has been mathematically demonstrated above.…”
Section: Discussionmentioning
confidence: 99%
“…An exact anatomical determination of the normal size of the esophageal hiatus is lacking. Shamiyeh et al [31] recently published the first study in which the normal size of a patient's esophageal hiatus is determined. The normal values, ranging up to 4 cm 2 , from this study done on cadaver subjects reflect the correct thresholds used in a recent study for tailoring the crural closure technique [21].…”
Section: Discussionmentioning
confidence: 99%